Competing for digital human capital: The retention effect of digital expertise in MNC subsidiaries - Grimpe, Christoph; Sofka, Wolfgang; Kaiser, Ulrich (Journal of International Business Studies, 2023)
Employees with relevant knowledge and skills for digitalization have become increasingly important for the competitiveness of MNCs. However, the shortage of such digital human capital in many host countries is putting pressure on MNC subsidiaries to prevent these employees from leaving. We theorize that the retention of digital human capital in MNC subsidiaries does not merely depend on salaries but crucially on the learning opportunities that subsidiaries offer. By integrating mechanisms from the literature on subsidiary-specific advantages into theoretical models explaining voluntary mobility constraints of employees, we reason that the opportunities for acquiring new skills in subsidiaries with advanced digital expertise will reduce the odds of losing these valuable employees. We test our theoretical predictions for 11,598 employees with digital human capital working for 866 foreign MNC subsidiaries in Denmark observed between 2002 and 2012. We find that digital expertise helps retaining digital human capital. The effect is stronger if subsidiaries have an internationally diverse workforce and when they possess patented technologies. Both factors provide distinct learning opportunities from digital expertise. The effect is weaker if the subsidiary is located in regional clusters of digital expertise since alternative employers may offer similar learning opportunities.